ALK -rearranged Mesenchymal Neoplasms With Prominent Foamy/Pseudolipogenic Cell Morphology : Expanding the Phenotypic Spectrum of ALK Fusion Neoplasms and Report of Novel Fusion Partners. - Agaimy, Abbas; Stöhr, Robert; Fisher, Cyril; Chrisinger, John S.A.; Demicco, Elizabeth G.; Tögel, Lars; Michal, Michal; Michal, Michael (American Journal of Surgical Pathology, 2024)
The category of ALK -rearranged mesenchymal neoplasms has been evolving rapidly, with reports of morphologically diverse lesions of cutaneous, soft tissue, and visceral origin. While some of these represent morphologically defined entities harboring recurrent ALK fusions (inflammatory myofibroblastic tumor and epithelioid fibrous histiocytoma), others are unclassified by morphology with variable overlap with the tyrosine kinase family of neoplasia and their underlying ALK fusions cannot be suspected based on morphology. We herein report 3 cases that expand the anatomic, morphologic, and genotypic spectrum of ALK -rearranged unclassified neoplasms. Patients were all adults aged 46 to 69 (median: 63) who presented with a mass located in the gingiva, subcutis of the back, and submucosal posterior pharyngeal wall. The tumor size ranged from 1 to 2.7 cm (median: 1.6). Conservative surgery was the treatment in all patients. Follow-up was available for one patient who remained disease-free at 14 months. Histologically, all tumors displayed large polygonal cells with foamy to granular and lipogenic-like microvacuolated copious cytoplasm and medium-sized round nuclei with 1 or 2 prominent nucleoli. Mitoses and necrosis were not seen. The initial diagnostic impression was PEComa, inflammatory rhabdomyoblastic tumor and unclassified pseudolipogenic neoplasm. Strong cytoplasmic ALK was detected by immunohistochemistry in all cases. Other positive markers include Cathepsin K (2/2), desmin (1/3), focal MyoD1 (1/1), focal SMA (1/3), and focal EMA (1/2). Targeted RNA sequencing revealed ALK fusions with exon 20 (2 cases) and exon 19 (one case) of ALK fused to RND3 (exon 3), SQSTM1 (exon 6), and desmin (intron 6). Methylation profiling in the desmin-fused case (initially diagnosed as inflammatory rhabdomyoblastic tumor) revealed an inflammatory myofibroblastic tumor match with a low confidence score of 0.5 and a flat copy number variation (CNV) profile. No NF1 mutation was detected in this case, altogether excluding an inflammatory rhabdomyoblastic tumor. Our study highlights and expands the morphologic and anatomic diversity of ALK- fused neoplasms and documents novel fusion partners ( RND3 and desmin).
EVALuna2:570327